Effect of Niclosamide (Bayluscide WP 70), Anacardium occidentale hexane extract and Euphorbia splendens latex on behavior of Biomphalaria glabrata (Say, 1818), under laboratory conditions - Jurberg, Pedro (1995)
Universidade do Estado do Rio de Janeiro, Instituto de Psicologia. Rio de Janiero, RJ, Brasil.